2020
DOI: 10.3390/su12041508
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Impacts on Basic Human Needs in the United States of America: A Panel Data Analysis

Abstract: This study empirically investigates the impact (overall, regional, and seasonal) of weather and climate extremes on basic human needs by employing a new poverty index, i.e., the Human Needs Index (HNI), in the United States of America. Detecting the contemporaneous correlations between errors, we apply second-generation unit root tests on monthly statewide panel data ranging from January 2004 to December 2018. The results obtained through cross-sectional time-series feasible generalized least square (i.e., FGL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The issues of serial correlation, panel group-wise heteroscedasticity, cross-sectional dependence and heterogeneity have not been taken into consideration in the literature (Mishra and Sahu, 2014;Loum and Fogarassy, 2015;Dumrul and Kilicarslan, 2017;Akram, 2012;Ansari et al, 2019;Praveen and Sharma, 2019b;Guntukula, 2020;Ansari et al, 2020). Only a few studies have considered these issues in their papers (Susanto et al, 2020;Ali et al, 2020). In this empirical work, we have added the other important variables that indirectly affect cereal production.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The issues of serial correlation, panel group-wise heteroscedasticity, cross-sectional dependence and heterogeneity have not been taken into consideration in the literature (Mishra and Sahu, 2014;Loum and Fogarassy, 2015;Dumrul and Kilicarslan, 2017;Akram, 2012;Ansari et al, 2019;Praveen and Sharma, 2019b;Guntukula, 2020;Ansari et al, 2020). Only a few studies have considered these issues in their papers (Susanto et al, 2020;Ali et al, 2020). In this empirical work, we have added the other important variables that indirectly affect cereal production.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Most research indicated a negative, mostly U-shaped relationship between renewable energy consumption and CO 2 reduction, whether for Asian countries (Muhammad & Khan, 2019)energy use, CO 2 emissions and capital role in the economic growth. This study applies generalized method of moments (GMM, African (Inglesi-Lotz & Dogan, 2018), OECD (Bilgili et al, 2016), the European Union (Muço et al, 2021), United States (Ali et al, 2020), 150 countries of the world (Cialani, 2017), or all economies (Dissanayake et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%